Structural Validity of Eureka Interest Inventory among Indonesian High School Student: An Analysis on Holland's RIASEC Model - Cucu Taqyah; Akhnaf, Ardhito Faza; Dumbi, Khairunnisa Syafira (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2024)
High school students are in the process of discovering their self-awareness. However, at this age, many high school students face confusion in making decisions about their vocational interest at their school, choosing between natural and social sciences. In response, the Eureka Interest Inventory (EII) was introduced and developed to assist students in measuring their vocational interests and abilities related to work activities based on the RIASEC Holland model. Therefore, the present study aims to assess the structural validity of the RIASEC Holland model among high school students and to determine any differences in validity based on gender and academic major. The sample population comprised 1609 high school students aged 17-19 years old. The validity of the measurement tool was evaluated using The Randomization Test of hypothesized Order Relations (RTOR) and analyzed using RStudio software. Additionally, the study used the Multidimensional Scalling (MDS) technique to describe the position of each RIASEC Holland personality type in graphical form. The results showed that the RIASEC Holland model has a good fit with the observed data. Additionally, no significant variations were observed in the fit of the model between male and female students, as well as between students majoring in natural and social sciences.